As traduções das obras de espiritualidade de Teodoro de Almeida (1722-1804) em Espanha e França : estado da questão, formas e tempos - Santos, Zulmira (1994)
Being a widely published author in Portugal, the oratorian Teodoro de Almeida (1722-1804) had also several of his works translated in Spain and France. The author tries to clarify which of the translations circulating under the name of Teodoro de Almeida are really his and to study the links between the translations of his spiritual works and the spreading of the devotions to the Virgin and to the Sacred Heart of Jesus. Finally, the author provides the list of the translations of Teodoro de Almeida’s works on spirituality published in Spain and France